Prevalence of 14 high-risk human papillomavirus subtypes among volunteers of cervical cancer screening by Papanicolaou smear cytology from a tertiary care institute of Assam, India - Pranay Kumar Phukan; Aparna Dutta; Ajanta Deuri; Gargi Choudhury; Porikhit Borpujari; Neelakshi Bhattacharyya; Gayatri Gogoi (Annals of Oncology Research and Therapy)
BACKGROUND: In India, cervical cancer is the second most prevalent cancer among women, constituting 18.3% of all cases. Persistent high-risk human papillomavirus (HPV) infection is a well-established risk factor for cervical cancer. OBJECTIVES: This study aimed to assess the prevalence of 14 high-risk HPV subtypes and their association with abnormal cytology among women in Upper Assam. MATERIALS AND METHODS: This descriptive cross-sectional study was conducted from February 2022 to April 2023 at a tertiary care center in Assam. A total of 100 women aged 23-72 years underwent cervical sample collection for HPV DNA analysis via real-time polymerase chain reaction and cytological examination of Papanicolaou (PAP) smears. RESULTS: The overall HPV prevalence was 13%, with 10% testing positive for HPV 16/18 and 6% for other high-risk subtypes. Coinfection with HPV 16/18 and other subtypes was found in 3% of cases. The mean age of HPV-positive participants was 46 years. Cytology results showed 87% normal, 11% inflammatory changes, and 2% epithelial cell abnormalities. The Chi-square analysis (α = 0.05) showed no significant association between age (P = 0.24), religion (P = 0.49), or education (P = 0.57) and HPV positivity, but the study showed a significant association of HPV infection with menstrual cycle (P = 0.04). The study also showed a significant association between cervical cytology and HPV positivity (P = 0.0087). DISCUSSION: The present study’s findings on the prevalence of all 14 high-risk HPV subtypes contribute new insights to the existing literature, although the slightly lower prevalence may be attributed to the sample size and demographic factors. The findings emphasize the need for regular screening by PAP smear as well as by HPV DNA detection, as cytological abnormalities were detected even in those without HPV infection. CONCLUSION: Along with 16/18 HPV subtypes, a longitudinal study may offer important insights into the development of coinfections and the other 12 subtypes of HPV infection, as well as the spectrum of dysplasia and in situ cervical cancer.